Synergistic Dual Antibacterial Activity of Magnetite Hydrogels Doped with Silver - Wehbe, Mohamad (Langmuir : the ACS journal of surfaces and colloids, 2024)
In this work, we utilized poly-N-isopropylacrylamide (NIPAM), magnetic nanoparticles (MNPs), and silver nitrate to prepare magnetic hydrogel microparticles doped with silver, which exhibited a dual antimicrobial effect. The antibacterial effect of these composites was mediated by the antimicrobial activity of silver and the magnetic hyperthermic induction, which we believe increased biofilm disruption and silver release into the surrounding bacterial biofilms. The prepared particles were characterized by using several analytical techniques. The particles exhibited a porous morphology impregnated evenly with silver nanoparticles, as observed by scanning electron microscopy (SEM). Furthermore, we examined the antibacterial activity of our microparticles against Escherichia coli by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Our findings revealed that the composites demonstrated significant antibacterial activity of up to 81% under magnetic hyperthermia as compared to 45% when samples were heated to the same temperature in a water bath at constant silver concentration. This demonstrates the distinctive inhibitory features of MNPs in enhancing bacterial killing when a magnetic field is applied. The findings of this study lay the groundwork for further exploration of microparticle-based antimicrobial therapies, which can contribute to the development of more advanced wound healing devices and better sterilization methods for medical devices